Materialsortering på digital plattform Eit steg mot høgare dataintegritet i den vitskaplege leksikografien - Bakken, Kristina; Grønvik, Oddrun (Nordiske Studier i Leksikografi, 2007)
For Norsk Ordbok 2014 linguistic documentation comes in the forms of scanned paper slips, electronic slips and corpus quotations, organised through the index system called the Meta Dictionary. Each entry in Norsk Ordbok is directly linked to the corresponding materials in the Meta Dictionary. However, with up to several thousand instances to sort into a complex entry structure, editors needed a sorting tool for classifying instances and storing the sorting itself. This would both improve editorial stringency, allow for variation in approach method and save time. This article, entitled Classifying instances of linguistic documentation on a digital platform – one step further towards data integrity within academic lexicography, describes the tool developed for Norsk Ordbok to meet this need, and sums up user experiences through the first two years as positive but still with space for improvement.